Home maintenance units based on a study of home conditions in Nacogdoches, Texas - Brown, Marjorie M., author; Williamson, Maude, advisor; Elliff, Rowan E., committee member; Marshall, Thomas O., committee member; Sackett, E. B., committee member; Thompson, Hazel E., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Interior decoration -- Study and teaching; Furniture -- Study and teaching